2013
DOI: 10.5586/asbp.2013.005
|View full text |Cite
|
Sign up to set email alerts
|

Soil preferences and morphological diversity of goldenrods (Solidago L.) from south-western Poland

Abstract: Species from genus Solidago are exceptionally successful worldwide invaders from North America [1]. Among about 120 Solidago species three are invaders, which so far have conquered Europe, large parts of Asia, Australia and New Zealand [2].In central Europe five representatives of the Solidago genus are found. Only one species (S. virgaurea L.) is native, while the other four are of American origin, namely: S. gigantea Aiton, S. canadensis L., S. altissima L. [S. canadensis var. scabra (Muhl.) Torr. and Gray] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 45 publications
2
45
0
1
Order By: Relevance
“…The growth of Calamagrostis epigejos is enhanced under low-intensity management regime [68], and under moist and nutrient-rich conditions [69]. Solidago gigantea also shows tendency to occur in relatively moist sites [70] and it commonly thrives in abandoned or sporadically mown grasslands [71]. More frequent occurrence of Calamagrostis epigejos and Solidago gigantea in more wet sites may also be the effect of irregular mowing of these sites that might be omitted by farmers due to the unfavorable ground conditions.…”
Section: Environment-vegetation Relationshipsmentioning
confidence: 99%
“…The growth of Calamagrostis epigejos is enhanced under low-intensity management regime [68], and under moist and nutrient-rich conditions [69]. Solidago gigantea also shows tendency to occur in relatively moist sites [70] and it commonly thrives in abandoned or sporadically mown grasslands [71]. More frequent occurrence of Calamagrostis epigejos and Solidago gigantea in more wet sites may also be the effect of irregular mowing of these sites that might be omitted by farmers due to the unfavorable ground conditions.…”
Section: Environment-vegetation Relationshipsmentioning
confidence: 99%
“…The species colonizes a given area in the form of single plants, patches or dense canopies. The giant goldenrod is much more prevalent in south-western and central Poland (Szymura and Szymura 2013;Kołaczkowska 2012), and it occurs far less frequently in the north-eastern part of the country (Korniak et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…There are many reasons for the ecological success of invasive goldenrods in Europe, including their considerable ecological tolerance: both species colonize habitats characterized by diverse soil texture, pH or nutrient content (Szymura and Szymura 2013;Pu_ zyńska et al 2012). Goldenrod populations develop rapidly due to very high levels of competitiveness and their allelopathic effects (Abhilasha et al 2008;Meyer and Hull-Sanders 2008;Yuan et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Length of residence time is significant for spread of invasive species -the probability that the log phase of invasion will start increases with the length of residence time (Kowarik 1995a;Sukkop and Wurzel 2003;Lockwood et al 2005;Groves 2006;Křivánek et al, 2006;Pyšek et al 2009). Szymura and Szymura (2013) claimed that predominance of one Solidago species over another is an effect of earlier establishment in the site of interest, which may explain the success of S. canadensis.…”
Section: Discussionmentioning
confidence: 99%
“…Both species increased their range after 1970 (Tokarska-Guzik 2005). Detailed study conducted by Szymura and Szymura (2013) in SW Poland, showed that S. gigantea was more numerous than other species of Solidago. S. canadensis and S. gigantea have very similar biologies, however they differ in urbanity indicator - Klotz et al (2002) found that S. gigantea is a moderately urbanophobous species and that S. canadensis is urbanoneutral.…”
Section: Discussionmentioning
confidence: 99%